Electrochemical enzyme-less urea sensor based on nano-tin oxide synthesized by hydrothermal technique. (5th December 2015) - Ansari, S.G.; Fouad, H.; Shin, Hyung-Shik; Ansari, Z.A.
Abstract: Nano-Tin oxide was synthesized using hydrothermal method at 150 °C for 6 h and then thin films were deposited by electrophoretic method at an optimized voltage of 100 V for 5 min on electropolished aluminum substrate. Spherical particles of about 30–50 nm diameters are observed with partial agglomeration when observed under electron microscope, which are tetragonal rutile structure. XPS results showed peaks related to Sn 4 d, Sn 3 d, O 1 s & C 1 s with spin–orbit splitting of 8.4 eV for Sn 3 d . Feasibility studies of enzyme less urea sensing characteristics of nano-tin oxide thin films are exhibited herein. The deposited films have been used for enzyme less urea sensing from 1 to 20 mM concentration in buffer solution. The sensors were characterized electrochemically to obtain cyclic voltammogram as a function of urea concentration and scan rate. The sensitivity is estimated as 18.9 μA/mM below 5 mM and 2.31 μA/mM above 5 mM with a limit of detection of 0.6 mM. Highlights: A simple method for synthesis of nano-tin oxide. Enzyme less Urea sensing characteristics of synthesized material. An attempt to design and develop enzyme less sensor and material.